Peran Lembaga Keuangan Syariah Terhadap UMKM yang Terdampak Pandemi COVID 19 di Indonesia - Kusjuniati, Kusjuniati (Widya Balina, 2020)
The period of the Covid-19 pandemic had a huge impact on public health around the world and a very heavy economic impact on various countries in the world including Indonesia. Almost all community economic activities were affected by this pandemic which caused company operations and other community economic operations to stop. Including UMKM activities in Indonesia which have experienced a downturn due to the Covid-19 pandemic. UMKM, which are people's economic activities, have contributed much to the Gross Domestic Product, which is 60.3% of the total GDP. UMKM absorb 97% of the workforce from 99% of the total employment. Therefore, to revive UMKM during the Covid-19 pandemic, it is hoped that the role of Sharia Financial Institutions (LKS) for UMKM so that they can return to carrying out economic activities throughout Indonesia. LKS that play a role in generating UMKM activities are Sharia Banking, Baitul Maal wat Tamwil and Baznas. ABSTRAK Masa pandemic covid-19 memberikan dampak yang begitu besar pada kesehatan masyarakat seluruh dunia dan dampak perekonomian yang sangat berat pada berbagai Negara di dunia termasuk Indonesia. Hampir semua kegiatan ekonomi masyarakat terkena dampak pandemi ini yang menyebabkan operasional perusahaan dan operasional ekonomi masyarakat lainnya terhenti. Termasuk kegiatan UMKM di Indonesia yang mengalami keterpurukan akibat pandemi covid-19. UMKM yang merupakan kegiatan ekonomi rakyat memberikan kontribusi tidak sedikit pada Produc Domestik Bruto yaitu sebesar 60,3% dari total PDB. UMKM menyerap 97% tenaga kerja dari jumlah 99% total lapangan kerja. Oleh karena itu untuk kembali membangkitkan UMKM dimasa pandemi covid-19 diharapkan peran Lembaga Keuangan Syariah (LKS) terhadap UMKM agar bisa kembali menjalankan kegiatan perekonomian di seluruh wilayah Indonesia. LKS yang berperan dalam membangkitkan kegiatan UMKM adalah Perbankan Syariah, Baitul Maal wat Tamwil dan Baznas.